Gamification user types and game playing preferences of university students - ÖZDENER DÖNMEZ, NESRİN (My University, 2021)
Students' widespread use of games has attracted scientists' attention, and it has been a matter of curiosity whether games can be used in education. The primary purpose of this descriptive study is to examine gamification user types of university students. In addition, the digital game playing characteristics and preferences of students were identified. The participants comprised one hundred and eighty-one (181) university students enrolled at a state university in Turkey. An online questionnaire prepared by researchers and the Gamification User Types Hexad Scale were used as data collection tools. Descriptive statistics (mean, percentage, frequency), Kruskal Wallis H, and chi-square analysis were utilized for data analysis. The results revealed that the highest ratio of students stemmed from achievers, philanthropists, and players. Furthermore, participants mostly preferred to play online games, and most of the students played digital games daily.
Keywords: Digital games; game preferences; game genre; gamification user types